2022
DOI: 10.3390/cells11121958
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Maintenance and the cGAS-STING Pathway in Cancer

Abstract: Cancer cells exhibit the unique characteristics of high proliferation and aberrant DNA damage response, which prevents cancer therapy from effectively eliminating them. The machinery required for telomere maintenance, such as telomerase and the alternative lengthening of telomeres (ALT), enables cancer cells to proliferate indefinitely. In addition, the molecules in this system are involved in noncanonical pro-tumorigenic functions. Of these, the function of the cyclic GMP–AMP synthase (cGAS)-stimulator of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 174 publications
0
5
0
Order By: Relevance
“…Compared with normal cells, cancer cells show remarkable features, such as continuous proliferation, abnormal DNA damage response (DDR), and high levels of ROS [ 12 ]. The occurrence of cancer is related to a variety of factors, such as genetic factors, environmental and chemical pollution, bad living and eating habits, emotional abnormalities, and some endogenous factors.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with normal cells, cancer cells show remarkable features, such as continuous proliferation, abnormal DNA damage response (DDR), and high levels of ROS [ 12 ]. The occurrence of cancer is related to a variety of factors, such as genetic factors, environmental and chemical pollution, bad living and eating habits, emotional abnormalities, and some endogenous factors.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from telomere maintenance, human telomerase reverse transcriptase was known to play roles in EMT, migration and invasion, angiogenesis, and activation of fibroblasts in malignant tumors [34][35][36], which may promote the formation of the immunosuppressive environment homeostasis of the TME. Mechanically, telomerase reverse transcriptase plays the role of a co-activator in the process of activating multiple signaling pathways, such as Wnt/β-catenin, PI3K/Akt, and cGAS-STING pathway [37][38][39]. Considering that telomerase reverse transcriptase might be regulated by some signaling pathways, a complex network of feedback mechanisms seems to exist between telomere maintenance and TME [40], which emphasizes the importance of telomere maintenance in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The cGAS-STING signalling pathway is part of the innate immune system that senses both host and foreign cytosolic double-stranded DNA to initiate a type I inter feron response ( Barber, 2015 ). Studies have shown an association between TMM and the cGAS-STING pathway, which contributes to cancer development ( Ebata et al, 2022 ). Spontaneous immortalisation of non-malignant cells induced by TERT expression has been reported to trigger the cGAS-STING pathway, thereby altering their microenvironment to become tumour-friendly ( Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%